Indústria criativa publicitária em Santa Maria/RS: modos de trabalho na publicidade local - (:unkn) unknown (Universidade Federal do Pampa, 2020)
This dissertation aims to investigate the ways of working in the advertising area in Santa Maria / RS, as a way to verify the configuration of the profession in the city and describe its main characteristics and practices. At first, the study reinforces the concepts of what resources are for work through theoretical reflections, such as the creative economy, creative industry, and advertising, for example, to understand issues related to advertising ways of working. For the development of the research, aspects are described of the bibliographic research and the exploratory research (MARCONI; LAKATOS, 2003) with an identification of the resident agencies in the city and, after that, the most advanced results of the questionnaires, instruments constituting the qualitative research (GIL, 2008). These instruments were addressed to advertising agencies and freelance professionals, with questions that address the professional profile and working modes. With an effective data collection, the results are described, highlighting the answers most commonly found in the research. In this way, recognizes the configuration of the Santa Maria advertising creative industry, while promoting local creative economy services.
Keywords: Publicidade; Trabalho qualificado; Agências de propaganda; Propaganda; Comunicação; Santa Maria, RS; Publicity; Skilled labor; CNPQ::CIENCIAS SOCIAIS APLICADAS